Strategy for Increasing Organizational Commitment through Strengthening the Effectiveness of Human Resource Management, Organizational Culture, Trust, and Perceived Organizational Support - Ani Interdiana Candra Sari; Bibin Rubini; Dian Wulandari (Riviera Publishing, 2024)
Organizations require high commitment from employees to achieve optimal goals, which can be improved through effective human resource (HR) management, a strong organizational culture, and a high level of trust. This research aims to identify optimal strategies, methods, and solutions to increase organizational commitment by strengthening the effectiveness of human resource management, organizational culture, and trust. Using a quantitative design and path analysis approach processed using SEM PLS, data was collected through a questionnaire to 139 foundation permanent teachers from 16 private high schools in South Jakarta City. The results of the study show that there is a positive and significant direct influence of the effectiveness of human resource management and organizational culture on organizational commitment. In addition, there is a positive and significant direct influence of the effectiveness of HR management on trust, but the direct influence of organizational culture on trust, as well as the direct influence of trust on organizational commitment, is not significant. It was also found that there was a positive but not significant indirect influence of the effectiveness of human resource management and organizational culture on organizational commitment through trust. The implications of this study emphasize the need for strategies to strengthen the effectiveness of HR management by improving compensation and maintaining positive aspects such as maintenance, HR planning, training and development, HR procurement, and performance appraisal. Organizational culture must be maintained through relationships between individuals, relationships with the environment, consistency of behavior, core values, and agreed norms.